Strengthening Grapevine Resistance by Pseudomonas fluorescens PTA-CT2 Relies on Distinct Defense Pathways in Susceptible and Partially Resistant Genotypes to Downy Mildew and Gray Mold Diseases - Lakkis, Sara; Trotel-Aziz, Patricia; Rabenoelina, Fanja; Schwarzenberg, Adrian; Nguema-Ona, Eric; Clément, Christophe; Aziz, Aziz (Frontiers in Plant Science, 2019)
Downy mildew caused by the oomycete Plasmopara viticola and gray mold caused by the fungus Botrytis cinerea are among the highly threatening diseases in vineyards. The current strategy to control these diseases relies totally on the application of fungicides. The use of beneficial microbes is arising as a sustainable strategy in controlling various diseases. This can be achieved through the activation of the plants own immune system, known as induced systemic resistance (ISR). We previously showed that bacteria-mediated ISR in grapevine involves both activation of immune response and priming state upon B. cinerea challenge. However, the effectiveness of beneficial bacteria against the oomycete P. viticola remains unknown and mechanisms underpinning ISR against pathogens with different life-style need to be deciphered. In this study we focused on the capacity of Pseudomonas fluorescens PTA-CT2 to induce ISR in grapevine against P. viticola and B. cinerea by using two grafted cultivars differing in their susceptibility to downy mildew, Pinot noir as susceptible and Solaris as partially resistant. On the basis of their contrasting phenotypes we explored mechanisms underlying ISR before and upon pathogen infection. Our results provide evidence that in the absence of pathogen infection, PTA-CT2 do not elicit any consistent change of basal defenses, while it affects hormonal status and enhances photosynthetic efficiency in both genotypes. PTA-CT2 also induces ISR against P. viticola and B. cinerea by priming common and distinct defensive pathways. After P. viticola challenge PTA-CT2 primes salicylic acid (SA)- and HR-related genes in Solaris, but SA and ABA accumulation in Pinot noir. However, ISR against B. cinerea was associated with potentiated ethylene signaling in Pinot noir, but with primed expression of jasmonic acid (JA)- and SA-responsive genes in Solaris, together with downregulation of HR-related gene and accumulation of ABA and phytoalexins.